Protective Effects and Mechanisms of Dendrobium nobile Lindl. Alkaloids on PC12 Cell Damage Induced by Aβ25-35 - Yuan Liu; Tingting Pi; Xiaohui Yang; Jingshan Shi (Behavioural Neurology)
Background. Aβ deposition abnormally in the mitochondria can damage the mitochondrial respiratory chain and activate the mitochondrial-mediated apoptosis pathway, resulting in AD-like symptoms. Objective. To observe the protective effects of Dendrobium nobile Lindl. alkaloids (DNLA) on Aβ25-35-induced oxidative stress and apoptosis in PC12 cells explore its possible protective mechanisms. Methods. PC12 cells were treated with DNLA with different concentrations (0.035 mg/L, 0.3 mg/L, and 3.5 mg/L) for 6 h, followed by administration with Aβ25-35 (10 μM) for 24 h. MTT assay and flow cytometer observe the effect of DNLA on Aβ25-35-induced cytotoxicity and apoptosis of PC12 cell. Based on the mitochondrial apoptosis pathway to study the antiapoptotic effect of DNLA on this model and its relationship with oxidative stress, flow cytometer detected the level of reactive oxygen species (ROS), and ELISA kits were used to detect superoxide dismutase activity (SOD) and glutathione (GSH) content in cells. The JC-1 fluorescent staining observed the effect of DNLA on the mitochondrial membrane potential (MMP) with inverted immunofluorescence microscopy. Western blot was used to detect the levels of mitochondrial apoptosis pathway-related protein and its major downstream proteins Bax, Bcl-2, cleaved-caspase-9, and cleaved-caspase-3. Results. DNLA can significantly improve the viability and apoptosis rate of PC12 cell damage induced by Aβ25-35. It also can restore the reduced intracellular ROS content and MMP, while SOD activity and GSH content increase significantly. The expression of apoptosis-related protein Bax, cleaved-caspase-9, and cleaved-caspase-3 decreased when the Bcl-2 protein expression was significantly increased. Conclusion. These findings suggest that it can significantly inhibit the apoptosis of PC12 cell damage induced by Aβ25-35. The mechanism may reduce the level of cellular oxidative stress and thus inhibit the mitochondrial-mediated apoptosis pathway.